Addressing the Affordable Housing Crisis for Vulnerable Renters: Insights From Broward County on an Affordable Housing Acquisition Tool. Issue 1 (2nd January 2016) - Walter, Rebecca; Evans, Aaron; Atherwood, Serge
Abstract : South Florida is experiencing an affordable rental crisis that is especially burdensome on those most vulnerable in society, low-income households. Rapid urbanization has resulted in inequitable land-use patterns that are a barrier to housing for the poor. As a solution to the crisis, local housing agencies seek to expand their affordable housing stock for vulnerable renters in opportunity-rich neighborhoods, but there is no standard framework for identifying properties for acquisition. Broward County serves as a case study to develop a housing acquisition tool. Using a combination of spatial statistics and principal components analysis, neighborhoods in which housing agencies may consider acquiring property are identified through the creation of an affordability surface in ArcGIS. Affordability is overlain by an opportunity surface derived from neighborhood quality and accessibility rankings. The results identify neighborhoods in Broward County that are both affordable and opportunity-rich, to better serve the county's most vulnerable renters.